P357 Long-term outcomes of biologic therapy in Crohn's disease complicated with internal fistulizing disease: BIOSCOPE study from GETECCU. (27th May 2021) - Rodríguez-Lago, I; Fernández-Clotet, A; Mesonero, F; García-Alonso, F J; Casanova, M J; Fernández-de la Varga, M; Cañete, F; de Castro, L; Gutiérrez, A; Sicilia, B; Cano, V; Merino, O; et al.
Abstract: Background: The prevalence of penetrating disease in Crohn's disease (CD) increases progressively over time, and evidence on the medical treatment of this complication is limited. The aim of this study was to evaluate the efficacy of biologic agents in CD complicated with internal fistulising disease. Methods: A retrospective analysis of all adult patients from the ENEIDA registry (>68, 000 patients) with CD who received at least one biologic agent -anti-TNF, ustekinumab or vedolizumab- for penetrating disease was performed. Exclusion criteria comprised treatment for perianal disease, enterocutaneous, anastomotic or periostomal fistula tracts. The main outcomes were fistula-related surgery and fistula closure on cross-sectional imaging. Preestablished secondary outcomes included the rate of abdominal abscess, the need for percutaneous drainage, the changes in the number of fistula tracts, fistula closure rates, and the safety profile.The baseline characteristics were analyzed by means of descriptive statistics and were compared by non-parametric tests. Predictive factors associated with surgery and fistula closure were evaluated by a multivariable logistic regression and survival analyses. Results: A total of 710 patients (median age 38 years [IQR, 28-48], 59% male, 55% L3) receiving 791 biologic treatments were included at 53 sites (701 anti-TNF, 71 ustekinumab, and 19 vedolizumab). Patients had a median of 1 (range 1-5) fistula tracts, 49% of them entero-enteric followed by entero-colic (28%). After a median follow-up of 59 months (IQR, 27-105), 244 patients (31%) required surgery due to internal fistulising complications after 8.5 months (IQR, 3-24). Patients with ileocolonic disease (OR 1.99 [1.22-3.23]), entero-urinary fistulas (OR 2.35 [1.17-4.73]), or with a stricture distal to the fistula (OR 2.1 [1.31-3.36]) showed a higher risk of surgery, with no differences between biologic drugs (Figure 1). Combination therapy reduced the risk of surgery (HR 0.58 [0.37-0.90]). Fistula closure was observed in 24% of patients after a median of 15 months (IQR, 7.5-27). Patients with a lower number of fistula tracts showed a higher probability of closure (OR 1.72 [1.09-2.7]). Conclusion: A high proportion of patients with internal fistulizing CD benefit from biologic treatment after a median of 5 years. During this follow-up, around two thirds of patients are free of surgery and one in every four patients achieves fistula closure.